Self-care food and its relationship with nutritional status in the national college of school application UNHEVAL- Huanuco 2015 - Veramendi Villavicencios, Nancy G. (2017)
To determine the relationship between self-care actions in food with nutritional status among high school. A correlational study with 142 students of the National School of Application UNHEVAL department of Huanuco was conducted during the period 2015. The data collection questionnaire self-care actions and an observation guide was used. For the inferential analysis the Chi -square test of independence was used. 88.0% (125 students) showed good nutrition and self-care in 60.6% (86 students) had normal state nutrition. Furthermore, it was found that the self in power is significantly related to nutritional status (X2 = 9.43; P≤0,024) and nutritional status of school is significantly related to self-care on the frequency of food consumption (X2 = 8.00; P≤0,046), food preparation (X2 = 7.86; P≤0,049) and food selection (X2 = 8.88; P≤0,031). There is significant relationship between self-care actions for food and nutritional status of secondary school Colegio Nacional de Huanuco UNHEVAL Application.